2013
DOI: 10.1021/ed300656p
|View full text |Cite
|
Sign up to set email alerts
|

Argument-Driven Inquiry: Using the Laboratory To Improve Undergraduates’ Science Writing Skills through Meaningful Science Writing, Peer-Review, and Revision

Abstract: This paper presents preliminary evidence supporting the use of peer review in undergraduate science as a means to improve student writing and to alleviate barriers, such as lost class time, by incorporation of the peer-review process into the laboratory component of the course. The study was conducted in a single section of an undergraduate general chemistry laboratory course offered at a large two-year community college located in the southeastern United States. The chemistry laboratory course was taught usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 10 publications
5
93
1
9
Order By: Relevance
“…The writing experiments report could be used to measure the students' critical thinking ability (Hoyo, 2003;Contakes, 2016). In addition, through the report writing, students could build arguments that were positively correlated to the oral communication ability (Walker & Sampson, 2013). Duzor (2016) reported that report writing could connect the theories and practices in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The writing experiments report could be used to measure the students' critical thinking ability (Hoyo, 2003;Contakes, 2016). In addition, through the report writing, students could build arguments that were positively correlated to the oral communication ability (Walker & Sampson, 2013). Duzor (2016) reported that report writing could connect the theories and practices in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this stage, basic theory can be strengthened and, hence, allows students to think through their inquiry design. Benefits of drafting an inquiry are that the students can build arguments, improve motivation, and it also produces meaningful learning not only for students but also for teachers (Walker & Sampson, 2013;Miller & Lang;Jean Burnham, 2013).…”
Section: Figure 4 Effect Of Od3r Methods For Scientific Attitudesmentioning
confidence: 99%
“…Writing reports has more advantages than answering questions at exams. In addition to constructing arguments, composing inquiry reports can hone critical thinking skills (Contakes, 2016;Walker & Sampson, 2013;Quitadamo & Kurtz, 2007). The ability to discuss inquiry in reports can relate theories studied in the classroom to laboratory investigation results (Duzor, 2016).…”
Section: Figure 4 Effect Of Od3r Methods For Scientific Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been noted that the benefits of instructor editing are not as strong as that of peer editing . Therefore, I propose that future use of this module incorporate a system of peer‐review as used in other similar research and writing paired assignments . Specifically, the third module session, even with the inclusion of a worksheet activity would have provided some down time for peer editing of introductions and methods to take place.…”
Section: Student Learning Outcomesmentioning
confidence: 99%